Neither Confirm nor Deny: Secrecy and Disclosure in Undercover Policing. Issue 3 (2nd September 2017) - Hadjimatheou, Katerina
Abstract : Recent scandals in U.K. undercover policing have prompted a public re-examination of the basis for continued secrecy with respect to cases in which serious historical misconduct is suspected. As part of its approach to balancing the competing demands of secrecy and accountability, the current legal process requires the police to provide case-by-case risk assessments of the harm to policing threatened by disclosure. This article considers the role of risk assessments in this process. It critically examines two arguments put forward by police in support of their claim that such assessments will nearly always support a refusal to disclose and thus a "neither confirm nor deny" response to requests for information about undercover policing. It argues that these arguments apply in fewer cases and/or less conclusively than police routinely suppose, and that their obligation to provide detailed case-by-case risk assessments therefore cannot be thereby evaded.